The role of trustee in Malaysia: comparative study between common law and Islamic law / Amirah Mohd Alias ...[et al.] - Mohd Alias, Amirah; Ahmad Zaini, Aimi Fadhilah Hazwani; Hasan, Ahmad Afiq; Yusof, Artika Nadia; Jamil, Nurul Shahernie (2010)
This research elucidates the concept of trustee comprehensively in both common law and Islamic law which comprises the appointment and removal of the trustee, delegation and remuneration of trustee, as well as the duty of the trustee towards the beneficiary. Furthermore, this research deals with the constitutional conflict with regards to the jurisdictional issues between common law and Islamic law in matters pertaining to trust and trustee in Malaysia. The legal position on Muslims trust and trustee in Malaysia has became a matter of controversy following the civil judicial scrutiny in matter concerning Islamic trust, inheritance, gift, and wakaf'm spite of the express provision declaring that those matters fall within the state and Syariah court jurisdiction. Thus, this research is designed to ascertain the inconsistency of the existing Trustee Act 1949 with Hukum Syara by comparing and contrasting the role of trustee under common law and Islamic law in Malaysia along with emphasizing the lacunae and the ambiguity of the statutory provisions that may adversely affect the process of Muslims trusteeship and the purpose of Muslims trust with a view to recommend possible solutions to the current legal conflict in Malaysia.